Social media marketing and customer purchase intention: Evidence-based bibliometrics and text analysis - Nguyễn, Văn Anh (Business Perspectives, 2024)
The rapid proliferation of social media platforms has sparked heightened interest among businesses seeking to leverage them to enhance customer purchase intentions. Consequently, there has been a surge in research exploring the intersection of social media marketing and consumer behavior. However, gaps persist regarding the primary themes within this research domain. This study analyzes 282 research papers spanning from 2012 to 2022, sourced from the Web of Science Core Collection, focusing on social media and customer purchase intentions. Leveraging Latent Dirichlet Allocation (LDA) commands in STATA and VOSviewer software, the study investigates emerging trends and prevalent themes, visualizing the dataset. The findings indicate a notable increase in research output, particularly from developed countries, with significant collaboration between developed and developing nations. Moreover, the study identifies five principal research topics: 1) the impact of social media marketing on consumer purchase intention, 2) the consequences of online brand communities on purchase behavior, 3) factors influencing consumer purchase intention, 4) influencer effects on purchase intention, and 5) social media advertising and marketing strategies. Future inquiries should delve into various factors shaping customer purchase intentions, including the role of influencers, word-of-mouth dynamics, and advertising strategies while considering the diverse cultural contexts across different regions. This comprehensive analysis provides valuable insights for researchers and practitioners alike, guiding future endeavors in understanding and harnessing the power of social media in consumer decision-making processes.